Trimeric hexa-dimethyltin-functionalized selenotungstate [{Sn(CH3)2(CH3COO)}3{Sn(CH3)2}3{Se2W18O62(OH)(H2O)}3]18−. Issue 16 (31st March 2016) - Chen, Wei-Chao; Qin, Chao; Wang, Xin-Long; Wu, Cai-Xia; Li, Yang-Guang; Zang, Hong-Ying; Shao, Kui-Zhan; Su, Zhong-Min; Wang, En-Bo
Abstract : The trimeric hybrid organic–inorganic selenotungstate(iv ) [{Sn(CH3 )2 (CH3 COO)}3 {Sn(CH3 )2 }3 {Se2 W18 O62 (OH)(H2 O)}3 ] 18− involving the first reported carboxyl-modified dimethyltin moieties exhibits photocatalytic H2 evolution activity. Abstract : The trimeric organic–inorganic hybrid selenotungstate(iv ) [{Sn(CH3 )2 (CH3 COO)}3 {Sn(CH3 )2 }3 {Se2 W18 O62 (OH)(H2 O)}3 ] 18− is composed of three Wells–Dawson-type {α-Se2 W18 } fragments and six {(CH3 )2 Sn 2+ } groups involving the first reported carboxyl-modified dimethyltin moieties, exhibiting photocatalytic H2 evolution activity.